(untitled) (Journal of Philosophy Culture and Political Science, 2023)
This study analyzes the definitions associated with the term digital transformation. Through this study, we aim to contribute to academic research and public discussion of the impact of digital transformation on scientific research. We focus on data infrastructures and their implications for research within and across disciplinary and national boundaries. The study aims to reflect and share our experiences with digital tools in the digital humanities, using approaches from research in science and technology, the history and philosophy of science. In addition, the ambivalent effects of digital transformation on the development of science are considered. The characteristics of digital transformation are analyzed. Issues between digital transformation and scientific ethics were considered. Key words: digitalization, digital transformation, scientific ethics, technology, democratic openness, access, open use, digital infrastructure, plagiarism, Internet space, scientific space.